Anti-Müllerian hormone, an ovarian reserve marker in hypogonadotropic hypogonadism. (June 2022) - Oncul, Mahmut; Ozcivit, Ipek Betul; Basibuyuk, Zafer; Cebi, Ceren; Sahmay, Sezai
Highlights: AMH levels reflect the follicle cohort in HH cases with negligible underestimation. AMH can be used as a sensitive marker for ovarian reserve in HH. Limit value of FSH < 3.05 IU/L and LH < 1.55 IU/L can be used for the diagnosis of HH. Abstract: Objective: To determine the usefulness of Anti-Müllerian Hormone (AMH) and antral follicle count (AFC) as an ovarian reserve marker in hypogonadotropic hypogonadism (HH) patients and to find a limit value for the gonadotropin levels in the diagnosis of HH patients. Study design: It is a retrospective cross-sectional single-center study. One hundred ninety-nine women with HH and 171 healthy controls with no cycle disorders were included into this study. Continuous variables were expressed as mean ± standard deviation. Statistical comparisons were carried out according to the intention to treat by Student's t -test, Mann-Whitney U test, where appropriate. Receiver operating characteristic curve-ROC was used to represent the sensitivity and specificity pair corresponding to decision threshold of FSH and LH levels in HH diagnosis. P < 0.05 was accepted to be statistically significant. Results: There was not any statistically significant difference between HH and control group regarding the age (23.94 ± 6.56 vs. 23.92 ± 3.01, respectively; p = 0.09 ) . Serum AMH levels didn't show statistically significant difference between HH and control group (3.26 ± 2.61 ng/mL vs. 3.15 ± 1.46 ng/mL, respectively ; p = 0.11 ) . The difference of AFC between HH and control group was statistically significant (6.67 ± 6.33 vs. 10.91 ± 2.92, respectively ; p < 0.001 ). Follicle-stimulating hormone (FSH), Luteinizing-hormone (LH) and Estradiol (E2 ) levels between the groups were found to be significantly different. Area under the receiver operating characteristic curve-ROC for FSH was 0.98 and for LH was 0.96. For the diagnosis of HH, FSH levels lower than 3.05 IU/L (with a sensitivity of 92% and specificity of 94%) and LH levels lower than 1.55 IU/L (with a sensitivity of 91% and specificity of 92%) can be used. Conclusion: In conclusion, serum AMH levels reflect the follicle cohort in HH cases validly with negligible underestimation of ovarian reserve. FSH < 3.05 IU/L and LH < 1.55 IU/L could be used with high sensitivity and specificity for the diagnosis of HH.